Strategic planning as a complex and enabling managerial tool. (13th September 2015) - Arend, Richard J.; Zhao, Y. Lisa; Song, Michael; Im, Subin
Abstract : Research summary : The role of the strategic planning process in the ongoing generation of innovative knowledge is vital to the survival and growth of a firm, especially when technologies and market conditions are rapidly changing. We analyze data from a survey of firms in high‐technology industries to determine whether it is possible to break the commonly experienced trade‐off between strategic planning's positive influence on firm profitability and its negative influence on firm innovation. We draw on Adler and Borys's (1996) conceptualization of bureaucratic process types to identify several firm characteristics that have the potential to affect whether employees perceive strategic planning as enabling to their creative endeavors. We find that contingent effects between strategic planning and the identified firm characteristics exist that can break the trade‐off . Managerial summary : A tension exits in the literature about whether strategic planning hurts or helps innovative activity. Our analysis of data from 227 business units in high‐technology industries indicates that strategic planning is a complex process that can be perceived by employees as enabling or coercive. Our results confirm that strategic planning negatively affects innovative activity but positively affects profitability for average firms. We find, however, controllable firm characteristics—risk‐taking and knowledge‐based reward systems—affect the trade‐off. Given the higher levels of risk‐taking and knowledge‐based reward systems, firms can use strategic planning to achieve both high returns on investment and a high level of innovative activity . Copyright © 2015 John Wiley & Sons, Ltd.